초산비닐수지계 접착제를 사용한 유리섬유강화플라스틱 복합집성재의 강도 성능 평가 - 박준철; Jun Chul Park; 홍순일; Soon Il Hong (목재공학, 2008)
This study was carried out to investigate the bending strength properties of the unreinforced glulam beams and the GFRP laminated glulam beams according to the volume ratio of GFRP. The 7-layer glulam beams ($10cm(b){×}14cm(h){×}180cm(l)$) were manufactured, using Larch (Larix kaempferi Carr.) laminae ($2cm(h){×}10cm(b){×}360cm(l)$), which were dried to the moisture content of 8% and specific gravity of 0.54. GPRP of 0.1 and 0.3 cm was reinforced between the outmost layer of bottom and next layer. When the glulam beams were reinforced with GFRP at the volume ratio of 0.7% and 2.1%, respectively, the bending strength was increased by 12% and 28%, respectively, in the reinforced beams than in control glulam beams. Also, the GFRP reinforced layer of the glulam beams with GFRP laminations blocked the progression of rupture, and the unbroken part held about 90% of the bending strength. In the results of glue joints test, the block shear strength is higher than $7.1N/mm^2$, the standard of KS F3021, and in the result of delamination, the adhesive strength is good as the water soaking and boiling delamination was less than 5%. 유리섬유강화플라스틱(GFRP : Glass fiber reinforced plastic) 보강 집성재를 제작한 후 유리섬유강화플라스틱의 체적비에 따른 휨강도 성능을 평가하였다. 집성재 제작에는 평균함수율 8%, 비중 0.54의 국산 낙엽송(Larix kaempferi Carr.) 제재판($2cm(h){×}10cm(b){×}360cm(l)$)을 7층으로 적층하여 집성재($10cm(b){×}14cm(h){×}180cm(l)$)를 제작하였다. 유리섬유강화플라스틱은 인장응력을 받는 하층의 최외각층과 윗층 사이에 두께 0.1 cm (체적비 0.7%)와 0.3 cm (체적비 2.1%)로 보강하였다. 유리섬유강화플라스틱을 체적비 0.7% 보강한 집성재의 경우 Control 집성재보다 휨강도가 12% 정도 증가하였으며 체적비 2.1%를 보강한 집성재의 경우 휨강도가 28% 정도 증가하였다. 또한, 유리섬유강화플라스틱 보강층이 파단의 진행을 억제하였으며 파괴되지 않은 부분은 약 90%의 휨강도를 유지하고 있었다. 접착성능 평가 결과 블록 전단 강도는 KS F3021의 합격기준 $7.1N/mm^2$를 만족하였으며 침지박리시험과 삶음박리시험 결과 박리율 5% 이하로 접착성능도 양호하였다.